Zootherapy in the Amazon: green anaconda ( Eunectes murinus ) fat as a natural medicine to treat wounds - Souza, Erika (Acta Amazonica, 2020)
Zootherapy (the use of the therapeutic potential of animals) is at least 6,000 years old, and has been kept active throughout generations until modern days. Animal fat is commonly used in the zootherapeutic folk medicine from South America, specially the green anaconda's fat, which is widely promoted as a natural medicine to treat wounds, even though there is no scientific evidence showing its efficacy. In this study we compared the total healing time and the proportional daily reduction of dorsal epithelial incisions in adult male Wistar rats treated with nitrofural (a commercial cicatrizing ointment) and with anaconda fat. We applied the treatments every two days and measured the incision diameter daily, during ten consecutive days. Differences among the groups in the total healing time and in the proportional daily reduction of the incision consistently showed that the fat-based treatment resulted in a faster healing process compared to the commercial ointment tested. The literature suggests that the efficacy of animal fat on healing may be primarily related to the presence of fatty acids, which have been widely demonstrated to be important for biochemical reactions involved in healing processes. Our findings are widely socially relevant, considering that traditional Amazonian communities that use anaconda fat in folk medicine do not have easy access to pharmacies and hospitals.